Diabetes and quality of life: Comparing results from utility instruments and Diabetes-39. Issue 2 (August 2015) - Chen, Gang; Iezzi, Angelo; McKie, John; Khan, Munir A.; Richardson, Jeff
Highlights Utility scores estimated from different MAU instruments differ significantly. MAU instruments could discriminate between the healthy public and diabetes patients. Mapping algorithms are reported to transform Diabetes-39 scales onto utility scores.